Work’s Environment Effect on Metal and Male Reproductive Hormones Levels: Circulating Testosterone, LH, and FSH are Positively Associated with Cadmium, Lead, and Molybdenum - Farha A.Ali Shafi (Journal of Global Pharma Technology, 2017)
Objectives: The present study was carried out to investigate the concentration cadmium (Cd.), lead (Pb.), and molybdenum (Mol.) in blood samples of petrol stations workers and its relationships with the male reproductive hormones levels such as follicle-stimulating hormone (FSH), luteinizing hormone (LH), and Testosterone. Methods: This study included 31 workers in 4 petrol station in different sites of Thi-Qar city/Iraq, who were working since more than 5 year in the petrol station and spend more than 12h work time, and ten healthy in different sites of a same city. Both groups age were ranged from 23 to 45 years old. Heavy material (Pb, Mo, and Cd) were determined by atomic absorption method using Shimadzu AA-7000 Dual Atomizer system. Hormones level (FSH, LH, and testosterone) were determined by enzyme linked fluorescent assay (ELFA) using the Bio Mérieux VIDAS Automated Immunoassay System. Results: Our results found significantly higher Cd, Mo, and Pb levels in Petrol workers compared to control (p<0.05). While no significantly differences were detected between FSH levels in control and Petrol workers groups, significantly higher testosterone level was found in Petrol workers compared to control (p<0.05). Conversely, significantly lower LH level in Petrol workers group than it in control group (p<0.05). Conclusion: the petrol station workers exposure to Cd, Pb, and Mol which lead to increase its levels in their blood due to neglect the occupational safety instructions. Thus associated positively with the testosterone level and negatively with the LH level in their blood.